Chewing Gum And Postoperative Ileus In Children After An Appendectomy In Terms Of Early Gut Motility, Resumption Of Feed, And Hospital Stay: Chewing gum and Postoperative ileus in children after an appendectomy - Rehana, Gulshan; Hanif, Sameen; Tasneem Kausar, Syeda Sidra; Raza, Zeeshan; Peter, Lubna (Pakistan Journal of Health Sciences, 2022)
Chewing gum usage decreases the postoperative ileus in kids who have had appendicectomies in terms of quick gut motility, feeding resumement, and hospital stay. Objective: The goal of this study was to determine how chewing gum affects early intestinal motility and how to avoid postoperative ileus in children who have had appendicectomies. Methods: In this study, children who had appendicectomies at a children’s hospital in Lahore underwent a randomized control experiment. This study included elderly pediatric patients between the ages of 5 and 18. Two groups—one serving as the control group and the other as the interventional group—were formed. 51 patients made up the study’s sample size, as determined by G power. In this study, 25 patients were placed in the control group and 26 patients were divided into the intervention and control groups. Results: In terms of early gut motility, early flatus pass, early bowel motions, early appetites, and early stool pass, gum chewing produced favorable effects in patients. Gum chewing can be effective in preventing intestinal paralysis or as a technique to improve gut motility after surgery, as it demonstrated early flatus, early bowel movements, early appetites, and early stool pass, protecting our children from the suffering of postoperative ileus. These metrics demonstrate how successful chewing gum is in preventing post-operative ileus in pediatric patients.Conclusions: The findings of this study demonstrated that chewing gum is one method for promoting oral intake, enhancing intestinal movement, and shortening the interval between the first flatulence and bowel movement